2013
DOI: 10.1016/j.ygcen.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of aromatase and estrogen receptors β in stem spermatogonia of bullfrogs indicates a role of estrogen in the seasonal spermatogonial mitotic activity

Abstract: Bullfrog stem spermatogonia, also named primordial germ cells (PGCs), show strong testosterone immunolabeling in winter, but no or weak testosterone immunoexpression in summer. Thus, the role of testosterone in these cells needs to be clarified. In this study, we proposed to evaluate whether PGCs express aromatase and estrogen receptors, and verify a possible role of estrogen in PGCs seasonal proliferation. Testes of male adult bullfrogs, collected in winter (WG) and summer (SG), were fixed and embedded in his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…In Lithobates catesbeianus estrogens play an important role in the control of primordial germ cells during the seasonal spermatogenesis (Caneguim et al, 2013a(Caneguim et al, , 2013b. Moreover, in juveniles Xenopus laevis estradiol (E 2 ) induces an acceleration of spermatogenesis (Hu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Lithobates catesbeianus estrogens play an important role in the control of primordial germ cells during the seasonal spermatogenesis (Caneguim et al, 2013a(Caneguim et al, , 2013b. Moreover, in juveniles Xenopus laevis estradiol (E 2 ) induces an acceleration of spermatogenesis (Hu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To study the RNA exosome during spermatogenesis, we analyzed the subcellular localization of its subunits LcRRP40, LcRRP42, LcRRP6 and LcRRP44 in testes of L. catesbeianus during the reproductive and quiescent periods, focusing on PGCs and interstitial cells because of the morphological changes they undergo in these periods [10, 11]. The results show that the exosome subunits were present in the cytoplasm of both interstitial cells and PGCs, in both periods (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The historesin sections were stained by Gill’s hematoxylin and eosin—H.E. [13], and the paraffin sections were subjected to immunohistochemical reactions as described [11].…”
Section: Methodsmentioning
confidence: 99%
“…FSH enhances the effects of LH, and acts on the Sertoli cells to promote the development of secondary spermatocytes into spermatozoa, as well as the synthesis of androgen binding proteins which maintain high levels of testosterone in the spermatogenic microtubules. The latter is one of the key factors necessary for maintaining spermatogenesis, and testosterone deficiency affects spermatogenesis, and the vitality and fertilization ability of the spermatozoa [3436]. Recent studies have shown that estrogen is almost involved in the whole process of spermatogenesis and is an essential hormone for spermatogenesis and maturation [3740].…”
Section: Discussionmentioning
confidence: 99%